MRI With Intratympanic Gadolinium: Comparison Between Otoneurological and Radiological Investigation in Menière's Disease - Neri, Giampiero; Tartaro, Armando; Neri, Letizia (Frontiers in Surgery, 2021)
Objectives/Hypothesis: To compare findings obtained using both magnetic resonance imaging plus intratympanic gadolinium and audiovestibular testing for Menière’s disease. Study Design: Retrospective cohort study. Methods: Patients with definite unilateral Menière’s disease (n=35) diagnosed according to 2015 Barany Criteria were included. Three-dimensional real inversion recovery (3D-real-IR) MRI was executed 24 hours after intratympanic gadolinium injection to assess the presence and degree of endolymphatic hydrops. Pure tone audiometry, bithermal caloric test, head impulse test, ocular and cervical VEMPs using air-conducted sound were performed to evaluate the level of hearing and vestibular loss. The results were compared to verify precision of the method in providing correct diagnoses. Results: Different degrees of endolymphatic hydrops were observed in the MRI of the cochlea and vestibule in the affected ears of Menière’s disease patients, even though it was impossible to radiologically distinguish the two otolithic structures separately. The correlation between the degree of linked alterations between instrumental and MRI testing was statistically significant. In particular, an 83% correspondence with audiometry, a 63% correspondence for cVEMPs and 60% correspondence for cVEMPs were seen. While for HIT the accordance was 70% and 80% for caloric bithermal test. Conclusions: MRI using intratympanic gadolinium as a contrast medium has proved to be a reliable and harmless method, even though there is an objective difficulty in disclosing macular structures. The study revealed that there is no complete agreement between instrumental values and MRI due to the definition of the image and fluctuation of symptoms. The present work highlights the greater (but not absolute) sensitivity of otoneurological tests while MRI, although not yet essential for diagnosis, is certainly important for understanding the disease and its pathogenic mechanisms.